Recent advances in iron-catalysed cross coupling reactions and their mechanistic underpinning. Issue 6 (24th February 2016) - Mako, T. L.; Byers, J. A.
Abstract : Advances in iron-catalysed cross coupling from 2010–2015 are critically reviewed. Abstract : Advances in iron-catalysed cross coupling from 2010–2015 are critically reviewed. In addition to a description of the systems that have emerged since 2010, the significant mechanistic work carried out to understand the mechanisms of these transformations will be discussed. An emphasis will be placed on mechanistic studies that utilize in situ reaction monitoring and the tools used to achieve this goal.